Numerical Study of Sediment Flow Over Bottom Intake Racks With Flow-3D - Zamanieh Shahri, Seyed Mahyar; Khoshnevis, Seyed Alireza; Bina, Keivan; Aboutalebi, Seyed Armin (International Journal of Scientific Research and Management (IJSRM), 2019)
Bottom intakes are the most useful structure for diverting the flow of steep rivers and providing specific amount of water for hydropower usage. It is crucial to obtain optimum of physical parameters in order to divert desired discharge with minimum possibility of occlusion. Numerical models can simulate flow and turbulence transport equations at any complex geometries. Numerical methods based on Computational Fluid Dynamics (CFD), are one of the most common methods of numerical simulation that is used in water structures. According to the capabilities of numerical methods, complex modes of flow field over bottom intakes can be analyzed. In the present study, Flow-3D software is used to investigate the experimental results of the previous researcher for sediment and clean water flow over bottom intake with circular bars numerically. This study is carried out in a total of 27 models for clean water and 9 models of sediment flow (Bed-Load) at different approaching flow conditions. Parameters of roughness, size of computational cell, turbulence transport equation, Bed Load Transport equation and bed load coefficient has been calibrated. Validation procedure proved that the accuracy and performance of numerical models appear to be acceptable for designing intake systems. For each test, the discharge coefficient is computed, then by using dimensional analysis, a dimensionless relation derived from the dependent and independent variables and compared with the measured discharge coefficient. Estimating the discharge coefficient by the proposed equation in clean water flow performed a mean error of 6.4 percent and for sediment flow led to a mean error of 4.3 percent.